Typology Of Up-To-Date States Considering The Present Condition Of The Statehood Of The Republic Of South Ossetia - S M Pliev (RUDN Journal of Political Science, 2014)
The article gives definitions to such terms as state and statehood, gives classification of types of states, such as a mini-state, a mega-state, a sovereign state and so on. Analyzing different types of states, the author tries to determine the type of the Republic of South Ossetia state